An O(c^k n) 5-Approximation Algorithm for Treewidth - Bodlaender, Hans L.; Drange, Pal Gronas; Dregi, Markus S.; Fomin, Fedor V.; Lokshtanov, Daniel; Pilipczuk, Michal (Annual Symposium on Foundations of Computer Science, 2013)
We give an algorithm that for an input n-vertex graph G and integer k > 0, in time O(c k n) either outputs that the tree width of G is larger than k, or gives a tree decomposition of G of width at most 5k + 4. This is the first algorithm providing a constant factor approximation for tree width which runs in time single-exponential in k and linear in n. Tree width based computations are subroutines of numerous algorithms. Our algorithm can be used to speed up many such algorithms to work in time which is single-exponential in the tree width and linear in the input size.